Southern Scholars in Goethe's Germany - Krumpelmann, John T. (UNC Studies in the Germanic Languages and Literatures, 1965)
This treasury of enlightening information reveals the roles of youthful Southerners in academic, scholarly, and literary society in Weimar, Göttingen, Bonn, Berlin, Heidelberg, and Munich in the Golden Age of Germany. In this piece of German-American cultural history, Krumpelmann traces the paths and influence of young men from the American South who attended German universities in the age of Goethe. Discussed are Hugh Legaré, Jesse Burton Harrison, George Henry Calvert, Thomas Caute Reynolds, Basil Lanneau Gildersleeve, James Woodrow, and others.